Pertanggungjawaban Pidana Pecandu dan Penyalah Guna Narkotika Berdasarkan Golongan - Khresna Wisantya; I Nyoman Gede Sugiartha; Anak Agung Sagung Laksmi Dewi (Jurnal Analogi Hukum, 2021)
The number of narcotics crimes is growing rapidly throughout Indonesia, these crimes are not only committed by Indonesian citizens but also committed by foreigners. That means international syndicates have made Indonesia not only as translit or circulation only but as a hotbed of international narcotics production. Narcotics crimes will affect the whole family, damaging the order and manners that once existed. In this case, narcotics abuse in Indonesia can result in a decrease in the quality of human resources owned by the community, especially in the country of Indonesia, in addition, it can also cause a loss to the country's finances. There are no problems (1) How is the arrangement of criminal sanctions against the narcotics of the drug group I until group III? (2) How is the EAS against narcotic abuse addicts that can be applied to group I until group III when reviewed from article 54 law number. 35 Years 2009? This research uses the normative method because there is still a vague norm, by being sourced to the opinion of the law scholars and the law. The positive law of narcotic criminal acts currently adheres to the double track system that judges can break abusers narcotics to be sentenced to prison and can also be placed in rehabilitation areas.